2008
DOI: 10.1134/s1075701508080126
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic-hydrothermal parkerite and associated minerals in the Noril’sk ore field

Abstract: Magmatic mineralization.Fe-Cu-Ni-Co sulfides are disseminated near the bottom and in other portions of the ore-bearing intrusions and make up massive orebodies, veins, and impregnations mainly in the lower contact zone of igneous rocks and in the adjacent wall rocks. The primary sulfide ore is composed of segregations of pyrrhotite-and chalcopyrite-group minerals; cubanite and pentlandite; products of solid-state modifications of the early hexagonal Mss = (Fe,Ni,Cu…)S and the late cubic Iss = (Fe,Cu,Ni…)S sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The ideal chemical formula for parkerite is reported as Ni 3 (Bi, Pb) 2 S 2 (Anthony et al 1990), due to the existence of limited substitution BiPb -1 in the parkeriteshandite series (Fleet 1973). Occurrences of parkerite with various Pb contents are described by Petruk et al (1969), Ondruš et al (2003) and Fojt et al (2008), andSpiridonov et al (2007) found at samples from Norilsk besides Pb-rich parkerite also its metacrysts with negligible Pb contents. The chemical analyses of Pb-free parkerite were published by Petruk et al (1969), Groves and Hall (1978) and Sejkora et al (2009).…”
Section: Paragenetic Position Textural Relations and Chemical Composition Of Ni-(biag) Sulphidesmentioning
confidence: 84%
See 1 more Smart Citation
“…The ideal chemical formula for parkerite is reported as Ni 3 (Bi, Pb) 2 S 2 (Anthony et al 1990), due to the existence of limited substitution BiPb -1 in the parkeriteshandite series (Fleet 1973). Occurrences of parkerite with various Pb contents are described by Petruk et al (1969), Ondruš et al (2003) and Fojt et al (2008), andSpiridonov et al (2007) found at samples from Norilsk besides Pb-rich parkerite also its metacrysts with negligible Pb contents. The chemical analyses of Pb-free parkerite were published by Petruk et al (1969), Groves and Hall (1978) and Sejkora et al (2009).…”
Section: Paragenetic Position Textural Relations and Chemical Composition Of Ni-(biag) Sulphidesmentioning
confidence: 84%
“…Fig.6Graph of Bi+Pb vs. Sb+As contents (apfu) for parkerite; published data has been taken fromPaar and Chen (1979),Ondruš et al (2003),Goryachev et al (2004),Rumsey and Savage (2005) andSpiridonov et al (2007).…”
mentioning
confidence: 99%
“…In addition, nickel can also form minerals with some complex anions containing bismuth, arsenic, and sulfur. Parkerite (Ni 3 Bi 2 S 2 ) and arsenohauchecornite (Ni 18 Bi 3 AsS 16 ), which have been described in other superlarge copper-nickel deposits such as Sudbury (Michener and Peacock, 1943;Springer, 1989) and Noril'sk (Ponomarenko et al, 1987;Spiridonov et al, 2008), have not been described in magmatic copper-nickel sulfides in China. However, they are reported for the first time in the present study.…”
Section: Distribution and Morphology Of Nickel-cobalt Mineralsmentioning
confidence: 99%
“…The ore-bearing intrusions of the Norilsk-Talnakh camp have the world's largest reserves of base metals and PGE (platinum group elements), making them a strategic resource for the future energy transition. Various studies have been carried out on specific deposits within this intrusive complex, resulting in the development of some genetic models [1][2][3][4][5][6][7][8][9][10][11][12][13][14], where physicochemical processes have played a key role in the formation of massive and disseminated ores. Interestingly, these models were primarily based on the spatial distribution of elements and minerals within the ore body.…”
Section: Introductionmentioning
confidence: 99%
“…The key idea underlaying this is that zoned ore bodies are formed by fractional crystallization of sulfide melts in magma chambers, e.g., [2][3][4][5]8]. However, alternative models, such as crystallization with fluid participation [6] or multiple-stage crystallization in flowing magma chambers have been proposed [9].…”
Section: Introductionmentioning
confidence: 99%